Knowledge, attitude, and practice toward foodborne disease among Chinese college students: a cross-sectional survey - Ma, Xingming; Bo, Li; Zhou, Xinmiao (Frontiers in Public Health, 2024)
BackgroundMore than 200 diseases are caused by eating food contaminated and the burden of foodborne disease is considered to be high worldwide. Foodborne diseases are an important public health issue, and the knowledge, attitudes and practices among college students are crucial in preventing outbreaks.ObjectiveThis study aimed to evaluate the current knowledge, attitudes, and practices (KAP) toward foodborne diseases among Chinese college students and to identify the factors influencing practice actions.MethodsA cross-sectional study was conducted from April to November in 2023. A cluster random sampling method was used to enroll participants at Xihua University. The questionnaire including 47 items was used to collect the foodborne diseases information. An offline questionnaire was used to generate the surveys. Multiple linear regression was used to analyze the factors associated with foodborne disease knowledge, attitudes and practices.ResultsA total of 445 college students with a mean age of 19.76 ± 1.24 years were included in the study. The majority of participants were female (59.1%), of Han Chinese (95.1%), and nearly two-thirds were lower-year undergraduates (66.7%). Most participants (78.9%) were non-medical students, and 64.7% of participants were from rural areas. The KAP score of foodborne diseases was 79.21 ± 6.84. The knowledge, attitudes, and practices scores toward foodborne diseases were 8.76 ± 0.95, 10.50 ± 1.63, and 59.94 ± 6.48, respectively. In particular, there was a notable decrease in practice scores toward foodborne diseases among male students, ethnic minority students, and non-medical students. The significant predictors of practices were included gender (β = 0.11, p < 0.05), nationality (β = −0.12, p < 0.05), specialization type (β = −0.13, p < 0.05), residence (β = −0.11, p < 0.05).ConclusionThese results revealed gaps in knowledge, attitudes, and practices regarding foodborne diseases, and the knowledge was at an insufficient level, the attitude was positive and practice was at a moderate and acceptable level. In general, the level of KAP was at a moderate and acceptable level. Gender, nationality, education level, specialization type, and residence were identified as crucial influencers on practices toward foodborne diseases. It is necessary to provide foodborne disease health education targeting this population in western areas, which can help improve students’ knowledge, attitudes, and practices.